Radial streak artifact reduction using phased array beamforming. Issue 6 (12th February 2019) - Mandava, Sagar; Keerthivasan, Mahesh B.; Martin, Diego R.; Altbach, Maria I.; Bilgin, Ali
Abstract : Purpose: A new method for streak artifact reduction in radial MRI based on phased array filtering. Theory: Radial imaging in applications that require large fields‐of‐view can be susceptible to streaking artifacts due to gradient nonlinearities. Coil removal methods prune the coils contributing the most to streaking artifacts at the expense of signal loss. Phased array beamforming is a form of spatial filtering used to suppress unwanted signals. The proposed method uses interference covariance generated from the streaking artifact samples which are manually extracted with phased array beamforming to suppress streaking in the images. Methods: The performance of the proposed method was evaluated on abdomen radial fast spin echo images acquired on a 1.5T Siemens scanner and compared with previously proposed methods. Results: Our results demonstrate that the proposed method can effectively suppress streaking artifacts without any noticeable loss in signal levels. Coil removal methods can suppress streaks as well but they may incur significant signal loss due to coil pruning. Quantitative metrics also demonstrate the superiority of the proposed method over earlier methods. Conclusion: The use of interference covariance with phased array beamforming can help reduce streaking artifacts.